Near‐Full‐Spectrum Emission Realized in a Single Lead Halide Perovskite across the Visible‐Light Region - An, Lian‐Cai; Li, Zi‐Ying; Azeem, Muhammad; Li, Wei; Qin, Yan; Gao, Fei‐Fei; Han, Song‐De; Wang, Guo‐Ming; Bu, Xian‐He (Angewandte Chemie International Edition, 2024)
The engineering of tunable photoluminescence (PL) in single materials with a full‐spectrum emission represents a highly coveted objective but poses a formidable challenge. In this context, the realization of near‐full‐spectrum PL emission, spanning the visible light range from 424 to 620 nm, in a single‐component two‐dimensional (2D) hybrid lead halide perovskite, (ETA)2PbBr4 (ETA+=(HO)(CH2)2NH3+), is reported, achieved through high‐pressure treatment. A pressure‐induced phase transition occurs upon compression, transforming the crystal structure from an orthorhombic phase under ambient conditions to a monoclinic structure at high pressure. This phase transition driven by the adaptive and dynamic configuration changes of organic amine cations enables an effective and continuous narrowing of the band gap in this halide crystal. The hydrogen bonding interactions between inorganic layers and organic amine cations (N−H⋅⋅⋅Br and O−H⋅⋅⋅Br hydrogen bonds) efficiently modulate the organic amine cations penetration and the octahedral distortion. Consequently, this phenomenon induces a phase transition and results in red‐shifted PL emissions, leading to the near‐full‐spectrum emission. This work opens a possibility for achieving wide PL emissions with coverage across the visible light spectrum by employing high pressure in single halide perovskites. Near‐full ‐spectrum emissions are achieved in a single component 2D lead halide perovskites by applying hydrostatic pressure.This work establishes a new pathway to achieve the PL full‐spectrum emission and provide valuable insights into the relationship between the HP‐PL emissions and high‐pressure phase transitions.